Problem-solving skills of high school students in chemistry - Maneerat Sa-ngiemjit; Ángel Vázquez-Alonso; María Antonia Manassero Mas (Institute of Advanced Engineering and Science, 2024)
People are continuously confronted with difficulties, which are situations that they do not understand yet strive to solve anyway. Researchers employed root cause analysis (RCA) in this study to analyze students’ problem-solving in chemistry and the students’ flaws and challenges in answering the subject. This research included 89 pupils from the secondary school’s science-mathematics department. Students determined strategies to calculate pH and the color of the blended solution after each indicator was dropped. This study’s qualitative method incorporates focus groups and content analysis. The majority of students properly identified the difficulty, and more than half correctly understood the problem. 100% of the pupils fared well in all processes since they were able to recognize and write all of the data. Using the RCA problem-solving technique, they were successful in identifying all of the data as potential causation aspects and the root causes of the problem. However, 37% of the pupils were unable to complete the problem. Investigating problem-solving flaws, it was determined that the students' defects in this problem-solving were application, analysis, practice, remembering, and time. Furthermore, researchers want to investigate the implementation of addressing the flaws in students’ problem-solving to better prepare them for efficient problem-solving.